PENYUSUNAN DAN IMPLEMENTASI SISTEM PELAYANAN PUBLIK SURAT PENGANTAR RT/ RW ONLINE UNTUK MEWUJUDKAN SEMARANG â€œSMART CITYâ€ - Khafid, Muhammad; Wahyudin, Agus (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2018)
Every citizen expects that RT / RW cover letter service can be obtained quickly and accurately. However, the expectation of public services such as introducing RT / RW letters sometimes can not be realized. Often the handling of RT / RW cover letters takes days. The purpose of this community service activity is to improve the quality of public service in the form of introductory letter service of RT / RW for the people in need. Specific targets of community service are: (1) establishment of public service system of RT / RW introduction letter online, and (2) implementation of public service system of RT / RW introduction letter online. Based on the results of community service activities, it is concluded that the RT RW online introduction letter application system is one of the alternative solutions for effective citizen administration services, since this system can overcome the difficulties of citizens in obtaining administrative services indefinitely dimensional space and time. The residents welcomed the existence of this RT RW online introduction letter application system, especially for residents of immigrant residents (residents of residential complex). However, for the original villagers, the existence of this system has not been so needed. The majority of the original villagers will not use this online system. Based on feedback on the ease of use of the system and the attractive appearance of this system, it is realized that the system is still a lot of shortcomings, so that future improvements are still needed.